Optimal overcurrent relay coordination for interconnected power systems: A proper approach and improved technique - Shanker D. Godwal; Kartik S. Pandya; Santosh C. Vora; Chintan R. Mehta; Vipul R. Rajput (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2023)
The optimum setting of directional overcurrent relays (DOCRs) is required to avoid miscoordination and avail fast response. To fulfill these requirements, it is required to prefer optimization techniques and modifications in objective functions (OF). Many researchers have adopted soft computing techniques and suggested modifications in the objective function for problem formulation of overcurrent relay coordination. Though these modifications and suggestions attain an optimum value of relay parameters, unfortunately, some of them don't follow the fundamental requirements of overcurrent relay coordination. This paper reflects on such modified objective functions and conveys a proper approach. Further, the paper proposes a new objective function as per the overcurrent relay coordination criteria. The novelty of the paper is to modify the existing objective function as per overcurrent relays coordination criteria and to add a new term in it to avoid miscoordination. The proposed objective function (POF) is applied on two power system test networks and results reveal that it is efficient and accurate.